2023
DOI: 10.3390/microorganisms11030603
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Assisted One-Step Synthesis of Electrode Materials for Li-Ion Batteries

Abstract: Mn(II)-oxidizing organisms promote the biomineralization of manganese oxides with specific textures, under ambient conditions. Controlling the phases formed and their texture on a larger scale may offer environmentally relevant routes to manganese oxide synthesis, with potential technological applications, for example, for energy storage. In the present study, we sought to use biofilms to promote the formation of electroactive minerals and to control the texture of these biominerals down to the electrode scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…MnOx is a strong oxidant and has been shown to have applications in catalysis, environmental remediation, and water oxidation [42,44,45]. For example, Guot et al recently reported the growth of manganese oxides on an electrode in order to construct a fuel cell [46]. Using nature as an inspiration for catalysis, we utilized biogenic manganese oxides from Pseudomonas putida strain MnB1 as a Mn(II)-oxidizing organism.…”
Section: Resultsmentioning
confidence: 99%
“…MnOx is a strong oxidant and has been shown to have applications in catalysis, environmental remediation, and water oxidation [42,44,45]. For example, Guot et al recently reported the growth of manganese oxides on an electrode in order to construct a fuel cell [46]. Using nature as an inspiration for catalysis, we utilized biogenic manganese oxides from Pseudomonas putida strain MnB1 as a Mn(II)-oxidizing organism.…”
Section: Resultsmentioning
confidence: 99%
“…Au, Ag, Cu, Pd, Mn) are now being considered for a wide range of industrial uses including water remediation, electrochemical energy storage, catalysis, and biomedical applications such as antimicrobial activity, bioimaging and biolabeling (e.g. Egan‐Morriss et al, 2022 ; Galezowski et al, 2023 ; Qin et al, 2020 ). Biomineralization of metallic nanoparticles presents several advantages over chemical or physical methods, such as improved particle stability and biocompatibility, as well as reduced environmental impact (Atalah et al, 2022 ; Carmona et al, 2023 ).…”
Section: Current and Potential Applications Of Biomineralized Materialsmentioning
confidence: 99%